UNDERSTANDING HOW HUMAN RESOURCE MANAGEMENT FUNCTIONS WITH NO HR DEPARTMENT: A CASE STUDY OF CRETIVOX - Rafiansyah, Naufal
Managing human resources in a company is essential for business growth. The absence of a Human Resource (HR) department has become a challenge for the business industry that relies heavily on human resources, such as creative industry. Cretivox Broadcasting Network as a digital media company shows significant growth in the past years without having any HR department in its structure. Questions emerge of how the company practices the Human Resource Management (HRM) functions and the employee experiences towards the practices. This research is written to provide an overview of the HRM functions practices in a company without an HR department and recommendations for future practices. The research data are gathered from interviews, observations, and literature studies. The interview respondents are 6 representatives of the company that have different backgrounds and job positions. The data analyzation process utilizes the narrative research method and is validated by using the triangulation method. The result shows that the company without an HR department can practice all of the HRM functions but it is not optimal yet. Acquiring, attending labor relations, health and safety, and fairness concerns functions are almost optimally implemented, while the training, appraising, and compensating need a lot of improvements. Based on this research, a company without an HR department can implement HRM functions optimally by learning and improving the lacking functions. In the future, as the employee numbers grow, the company could consider adding an HR department to its structure.